Optimization and Evaluation of Aceclofenac Loaded Solid Lipid Nanoparticles via Response Surface Methodology - Khadija Saleem; Nariman Shahid; Badarqa Tul Ayesha; Alia Erum; Amna Wajdan; Kashif Barkat; Ume Ruqia Tulain; Muhammad Umer Ashraf; Sana Hanif (Journal of Pharmaceutical Innovation, 2027)

Genome-wide characterization and comparative analysis of Bacillus paranthracis MBBL1 reveals genomic plasticity features - Nimra Hanif; Muhammad Naveed; Maida Salah Ud Din; Tariq Aziz; Ashwag Shami; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2026)

Presolidification column design modification based on simulation of ammonia flow distribution for external gelation coated particle fuel kernel surrogates fabrication - Muhammad Rizky Akbar Pradana; Muhammad Ilham Bayquni; Hanif Ghufron; Sugeng Rianto; Gagad Rahmadi; Praditya Vankabo; Ratih Langenati (Annals of Nuclear Energy, 2026)

Stable isotopes and larger benthic foraminiferal response to the Paleocene-Eocene Thermal Maximum in the shallow-water carbonates of the Lower Indus Basin (Eastern Tethys, Pakistan) - Hafiz Shahid Hussain; April N. Abbott; Stefan C. Löhr; Muhammad Hanif; Sean T. Murray; Mohibullah Mohibullah; Mukhtiar Ghani (Journal of Asian Earth Sciences, 2026)

Development and Characterization of Proliposomes for Sustained Oral Delivery of the DPP-4 Inhibitor Vildagliptin - Shazia Ashraf; Asadullah Madni; Faizan Akram; Muhammad Farhan Hanif; Afifa Shafiq; Iqra Fatima Ayub (Journal of Pharmaceutical Innovation, 2026)

Geochemistry and sedimentology of cretaceous oceanic red beds (CORBs) of the Turonian Goru Formation (Sulaiman Range, Pakistan) - Ahmed Nur Dalmar; Shuja Ullah; Muhammad Hanif; Mahnoor Sabba; Abdalle Dahir Yusuf; Muhammad Rizwan (Journal of African Earth Sciences, 2026)

Nano-enabled spray-induced RNA interference against fungal pathogens of oilseed crops: carrier performance, delivery evidence and field translation - Amjad Ali; Sana Hanif; Afifa Azad; Kanza Azad; Tehreem Eraf; Muhammad Aasim; Ashrit Gulfraz; Faheem Shehzad Baloch; Muhammad Shahbaz (World Journal of Microbiology and Biotechnology, 2026)

Performance of hybrid cooling control for the thermal storage effect of PCM-integrated floor in hot-humid climates - Tianxing Zhang; Muhammad Emir Hanif Rasyadi; Haruka Kitagawa; Takashi Asawa (Building and Environment, 2026)

Integrated carbon dioxide capture and nutrient removal from food waste digestate: A microalgae-assisted process in a smart photobioreactor for enhanced environmental performance - Titin Handayani; Prasetiyadi Prasetiyadi; Amita Indah Sitomurni; Akhmad Rifai; Nuha Nuha; Arief Barkah; Djatmiko Pinardi; Firman L. Sahwan; Sri Wahyono; Feddy Suryanto; Suprapto Suprapto; Diyono Diyono; et al. (Biomass and Bioenergy, 2026)

Recent Advances in Heterogeneous Solar Photocatalytic Reactors for Wastewater Treatment - Muhammad Asif Hanif; Khurram Shahzad; Sara Yaqoob; Arshid Mahmood Ali (Water Conservation Science and Engineering, 2026)

Potential Application of Tamarind Seed Extract as Coagulant Aid in Alum-Based Removal of Polyamide Microplastics - Muhammad Adli Hanif; Naimah Ibrahim; Man Yung Ho; Masitah Hasan; Farrah Aini Dahalan; Nabilah Aminah Lutpi; Norzila Othman; Mohamed Hasnain Isa (International Journal of Environmental Research, 2026)

Nanoparticles of thiolated gum ghatti for the controlled ocular delivery of Ciprofloxacin - Muhammad Abu Sufian; Shahid Shah; Akhtar Rasul; Nabeel Ahmad; Ghulam Abbas; Muhammad Hanif; Saleha Babar; Azka Fatima; Omeira Iqbal; Maira Tahir; Nader I. Namazi (DARU Journal of Pharmaceutical Sciences, 2026)

First molecular record of Panaeolus subbalteatus (Psathyrellaceae, Agaricales) from Pakistan - Saliha Rukhsar; Nousheen Yousaf; Sadaf; Mahneem Fazal; Muhammad Hanif; Murad Muhammad; Dilfuza Egamberdieva; Wen-Jun Li (Antonie van Leeuwenhoek, 2026)

Computational identification of natural phytochemicals as potential inhibitors of UBE2J1 causing ovarian cancer - Zujaja Rehman; Ejaz Rasul; Wisha Asif; Rabail Afzal; Nouman Ali; Nimra Hanif; Muhammad Salik Kamran (In Silico Pharmacology, 2026)

Pseudomonas aeruginosa ST4936 with extensive antibacterial drug resistance and virulence determinants from ureteral stent biofilms: whole-genome insights - Nargis Khan; Rani Faryal; Muhammad Hanif Khan; Liaqat Ali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Synergistic adsorption and visible-light driven photocatalysis using WO3/ZnO n-n type II heterojunction for tetracycline-contaminated wastewater treatment - Andri Cahyo Kumoro; Muhammad Itsar Hanif; Meitri Bella Puspa; Febio Dalanta; Tutuk Djoko Kusworo (Journal of Environmental Chemical Engineering, 2026)

Comparison of Different Extraction Methods on Potato Starch Properties - Sadia Ansar; Imran Pasha; Rana Muhammad Aadil; Muhammad Asif Hanif (Potato Research, 2026)

Advances in Coated Urea Technology: Toward Climate-responsive, Microbiome-friendly, and Site-specific Nitrogen Management - Ayesha Mustafa; Imran Khan; Muhammad Umer Chattha; Shazia Hanif; Aqsa Andleeb Sial; Muhammad Umair Hassan; Tahani A.Y. Asseri; Rehab O. Elnour (Journal of Soil Science and Plant Nutrition, 2026)

Comparative effect of malting on nutritional profile, malting properties and structural characteristics of barley, corn, and rice - Husnain Rasheed; Imran Pasha; Muhammad Atif Randhawa; Muhammad Asif Hanif (Cereal Research Communications, 2026)

Mucin-Based Biomimetic Patches for Dynamic Heart Repair: Auxetic Structures and Translational Challenges - Rishatani Gunasegaran; Rania Hussien Al-Ashwal; Norhana Jusoh; Muhammad Hanif Ramlee; Sadeq M. Al-Hazmy (Cardiovascular Engineering and Technology, 2026)
Purpose This scoping review examines strategies to improve adhesion and integration of epicardial patches within the dynamic and wet cardiac environment. It emphasizes mucin-based bioadhesives and auxetic designs as potential solutions for long-term tissue-conformal myocardial repair. Methods Approximately 150 peer-reviewed articles published between 2010 and 2024 were identified through a structured literature search conducted across PubMed, Scopus, and Web of Science. The studies cover adhesive biomaterials, structural patch designs, and epicardial tissue repair approaches were screened and thematically synthesized to map current advances, limitations, and translational gaps. Results Commercially available epicardial patches fail to maintain adhesion under cyclic loading and fluid-rich conditions. Among bioadhesives, mucin demonstrates promising wet adhesion, viscoelasticity, and biocompatibility. Nonetheless, its translation is limited by batch-to-batch variability, purification challenges, and potential immunogenicity. Dopamine-, hyaluronic acid-, and alginate-based adhesives provide alternatives but remain constrained by oxidative instability, limitted long-term durability, or inadequate mechanical performance. Structural innovations such as auxetic geometries improve patch flexibility, strain distribution, and conformability compared with multilayered or microneedle-based strategies. However, challenges related to fabrication, sterilization, scalability and potential interference of cardiac anatomy andphysiology require further investigation. Conclusions The synergistic integration of mucin-based adhesives with auxetic designs presents a compelling pathway toward durable, biocompatible, and tissue-conformal cardiac patches. Addressing manufacturing scalability, reproducibility, and immunological safety will be critical to advancing these concepts toward clinical applications.

A parsimonius agroclimatic methodology to assess the hydrological sustainability of agriculture in the Mediterranean semiarid climate - Stefano Barontini; Martina Greta Caffi; Muhammad Faisal Hanif; Elpida Kolokytha; Dimitrios Malamataris; Hiba Mohammad; Marco Peli (Hydrological Sciences Journal, 2026)

Amine-appended bimetallic MOF-74 for highly selective and energy-efficient CO₂ capture under vacuum swing adsorption - Rodynah A. Alabdulhadi; Shabnam Khan; Md Delowar Hossain; Aamir Hanif; Mohammed Ahmed Sanhoob; Mohd Yusuf Khan; Mosim Ansari; Aasif Khan; Muhammad Usman; Saleh AlMansour; Aasif Helal (Chemical Engineering Journal, 2026)

A mixed carbonate-siliciclastic foreland basin system: An example from the Upper Cretaceous Muti Formation, Jabal-Akhdar Dome, Oman Mountains - Jenan Ahmed Attar; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al-Sayigh; Mohamed S. H. Moustafa; Muhammad Qasim (Facies, 2026)

Forecasting future instability hazards at Anak Krakatau volcano, Indonesia, using archival reconstructions of edifice evolution - Kerys Meredew; Sebastian F. L. Watt; Mike Cassidy; Achmad Fakhrus Shomim; Muhammad Edo Nurshal; Mirzam Abdurrachman; Muhammad Hanif; Wilfridus F. S. Banggur; Dini Nurfiani; Samantha Engwell; Victoria C. Smith; Chiara M. Petrone; et al. (Bulletin of Volcanology, 2026)
Volcanic lateral collapses represent major hazards through associated eruptive activity, landslide inundation and, in island or coastal settings, the generation of tsunamis. Forecasting the timing, precursory indicators, and magnitude of lateral collapses still remains a significant gap in volcanic risk management, a challenge exemplified by the 2018 lateral collapse of Anak Krakatau, Indonesia. The volcano’s southwestern flank collapsed without recognised warning, resulting in a devastating tsunami which inundated > 300 km of regional shorelines. Since then, the edifice has rapidly regrown, prompting a necessary assessment of its future stability. Here we analyse Anak Krakatau’s uniquely detailed archival growth records, in combination with satellite and drone datasets, to reconstruct historical edifice development from 1919 to 2023, using this to then project and contextualise its future growth trajectories and assess potential instability conditions. Our time series of 3D models reveals that post-collapse regrowth has mimicked historical development trends, but on a considerably accelerated timescale. If future growth follows the long-term pre-collapse (1960–2018) average, then a subaerial edifice morphology equivalent to 2018, but with larger overall dimensions, would be met by around the year 2100. If future development maintains the much higher 2019–2023 growth trends, then a morphology comparable to 2018 could instead be reached by the 2030s. We consider the continuation of such high growth rates unlikely, but this highlights the importance of monitoring edifice growth and flank instability signals over the coming decades, following the methodology provided here. Additionally, the submarine SW flank now has a considerably reduced gradient relative to 2018, which is likely to promote stability further into the future. To comprehensively assess future stability, the role of alteration, hydrothermal activity and the structure of the submarine flank should also be evaluated.

CRISPR-Cas9 and next-generation gene editing strategies for therapeutic intervention of neurodegenerative pathways in Alzheimer’s disease: a state-of-the-art review - Muhammad Sohail Khan; Imran Zafar; Adil Jamal; Fayez Saeed Bahwerth; Samiullah Khan; Muhammad Faizan; Hanif Khan; Muhammad Noman; Kendrix Okeibunor; Ashfaq Ahmad; Muhammad Zain Ul Abedin (Acta Neurologica Belgica, 2026)

Technological advances and sustainable pathways for electrolytic wastewater treatment - Rabia Shaheen; Muhammad Asif Hanif; Soroush Abolfathi (Journal of Water Process Engineering, 2026)

Mineral chemistry and alteration characteristics of sulfide-bearing metavolcanics in the Thalle area, Kohistan–Ladakh Arc: insights into magmatic-hydrothermal fluid evolution - Muhammad Farhan; Tehseen Zafar; Mohammad Arif; Chun-Feng Li; Zahid Hussain; Zaheen Ullah; Syed Wajid Hanif Bukhari; Uzair Siddique; Syed Ali Turab; Mubasir Ali (Geosciences Journal, 2026)

Multifunctional Curcumin Nanoparticles: Oncolytic, Radical Scavenging, Regenerative, Hepatoprotective, and Bactericidal Effects - Huzaifa Hanif; Shahzad Hussain; Umer Rashid; Tafail Akbar Mughal; Muhammad Naeem Ahmad; Muhammad Waseem (Cell Biochemistry and Biophysics, 2026)

Microplastic exposure reduces multi-trophic biomass yield in a freshwater integrated aquaculture system - Gökhan Tunçelli; Muhammad Hanif Azhar; Devrim Memiş; Nuray Erkan; Idil Can-Tuncelli; Özkan Özden; Eda Dagsuyu; İsmet Burcu Turkyilmaz Mutlu; Refiye Yanardag (Aquaculture International, 2026)
Freshwater integrated multi-trophic aquaculture (IMTA) systems are increasingly used to enhance nutrient utilization efficiency; however, their performance under microplastic (MP) exposure remains poorly characterized. This study evaluated the effects of water-borne and feed-borne polyethylene (PE) MP (10–20 µm) on biomass production and filtration performance in a three-compartment freshwater IMTA system comprising rainbow trout ( Oncorhynchus mykiss ), freshwater mussels (Unionidae), and duckweed ( Lemna minor ). Fluorescent spherical MPs were applied in four treatments ( n = 3 tanks per treatment): control (no MPs), feed-borne MPs (5 particles per 100 g feed), water-borne MPs (35 particles L⁻ 1 at fish-tank inflow), and combined exposure. The exposure phase lasted 45 days with 15-day sampling intervals, followed by a 45-day depuration phase. Fish growth responses differed modestly among treatments during exposure, with transient reductions observed in MP-exposed groups relative to the control at intermediate sampling points. Mussel filtration capacity showed limited variation among treatments, with no consistent treatment-specific suppression across time. Duckweed biomass accumulation was lower under combined exposure compared with the control, whereas variability was higher in MP treatments during early growth stages. An integrated multi-trophic performance index calculated from terminal measurements indicated moderate reductions in overall system productivity under combined exposure relative to the control. During depuration, growth trajectories across treatments converged. These results indicate that elevated microplastic exposure can influence biomass distribution and productivity within freshwater IMTA systems, particularly under combined exposure scenarios.

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Olive waste valorization: advances in nutrient optimization and microbial engineering for lipid production - Sana Akbar; Muhammad Zubair; Asma Hanif; Sobia Kunbhar; Aisha Zulfiqar; Shakila Rahman; Zubia Rahim; Kalim Ullah (Bioresource Technology, 2026)

Detection and serotyping of bluetongue viruses in Khyber Pakhtunkhwa Province, Pakistan - Muhammad Ishaq; Syed M. Jamal; Syed Asad Ali Shah; Hanif Ur Rahman; Alessandra Leone; Liana Teodori; Maura Pisciella; Ottavio Portanti; Cesare Cammà; Valentina Curini; Maurilia Marcacci; Barbara Secondini; et al. (Tropical Animal Health and Production, 2026)

Combining anxiolytic activity of thymol and trans-ferulic acid: a potential GABAergic intervention - Md. Hanif Munshi; Noshin Tasnim Yana; Imam Hossen Rakib; Emon Mia; Nusrat Jahan Tohfa; Md. Sakib Al Hasan; Md Abu Sayeed; Mst. Sumaia Akter; Md. Arif Hossain; Muhammad Torequl Islam; Md. Shimul Bhuia; Mushtaq Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Impact of CuS Nanoparticles on Morpho-Biochemical Traits and Yield in Two Oilseed Crops; Eruca Sativa and Linum Usitatissimum - Jehangir Khan; Mah Rukh; Saad Hanif; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Sugarcane varietal classification using remote sensing and AI: a comprehensive review and future roadmap - Shehryar Attaullah Khan; Musharif Ahmed; Naurin Farooq Khan; Muhammad Hanif (International Journal of Remote Sensing, 2026)

Holocene surface-rupturing earthquakes on the Matano fault in the Mahalona basin, Sulawesi, Indonesia - Adi Patria; Muhammad Hanif; Anggraini Rizkita Puji (Tectonophysics, 2026)

Pathways to net zero: Scenario analyses of urban building stocks in Jakarta - Hanif Hanif; Ahmed Z. Khan; Muhammad Idrus Alhamid; Yohei Yamaguchi (Energy and Buildings, 2026)

A review on the earth observation techniques for coastal vulnerability index in Malaysia - Shin Yi Chen; Nurul Hazrina Idris; Mohammad Hanif Hamden; Amalina Izzati Abdul Hamid; Muhammad Faiz Pa’suya; Norhadija Darwin (International Journal of Remote Sensing, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Morphological, Biochemical, Yield, and Metal Accumulation Response of Eruca sativa (L.) and Linum usitatissimum (L.) by MnS NPs Application - Jehangir Khan; Mah Rukh; Saad Hanif; Amina Afzal; Muhammad Zia (Journal of Plant Growth Regulation, 2025)

Enhancing environmental quality and mitigating climate change: a renewable energy policy perspective based on evidence from most polluted European countries - Muhammad Sadiq; Muhammad Atif Nawaz; Fengsheng Chien; Arshian Sharif; Sobia Hanif (Gondwana Research, 2025)

Soil Pollution in Urban Environments: Sources, Consequences, Potential Mitigation Strategies and the Importance of Sustainable Urban Development - Muhammad Nauman Hanif; Ian Bartican Benitez (Water, Air, & Soil Pollution, 2025)

Endophyte Bacterial Metabolites: An Active Syrup for Improvement of Growth, Biomass, and Antioxidant System of Zea mays L. in Drought Condition - Mahwish Salman; Muhammad Rizwan Javed; Anam Tariq; Muhammad Usama; Hafiza Iqra Hanif; Bushra Sadia; Shazia Naheed (Journal of Plant Growth Regulation, 2025)

Genome-wide identification, characterization, and functional analysis of the myb transcription factor family in chickpea (Cicer arietinum) - Muhammad Afzal; Hira Nawaz; Sadia Hanif; Muhammad Habib Ur Rahman; Abdel-Halim Ghazy (Genetic Resources and Crop Evolution, 2025)

The possible contribution of marine heatwaves on the declining healthy coral reef cover in Nusa Dua, Bali - Muhammad Azzam Hanif Prasetyo; Diah Permata Wijayanti; Dwi Haryanti; Toshio Suga; Ardiansyah Desmont Puryajati; Sayaka Yasunaka; Anindya Wirasatriya; Syifa Fauziah; Rizki Taqwa Putranto; Hanani Adiwira; Maria Vanessa B. Rodriguez; Parichat Wetchayont; et al. (International Journal of Remote Sensing, 2025)

Ring opening of epoxides: a facile approach towards the synthesis of polyketides and related stereoenriched natural products: a review - Madiha Hanif; Asim Mansha; Kulsoom Ghulam Ali; Muhammad Athar Saeed; Shahid Mahmood; Aijaz Rasool Chaudhry; Ahmad Irfan; Aqsa Mushtaq; Ameer Fawad Zahoor (Molecular Diversity, 2025)

Exogenic Application of Cinnamon Oil and Salicylic Acid Inhibits Alternaria Fruit Rot of Peach by Stimulating Defense-Related Enzymatic Activities - Sadia Hanif; Ambreen Maqsood; Muhammad Naveed Aslam; Muhammad Taimoor Shakeel; Atta ur Rehman; Mohammad Shafiq u Rahman; Shah Saud; Khaled Al-Kahtany; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Effectiveness of curcumin for anticancer activity by surface functionalized nickel and manganese ferrites - Huzaifa Hanif; Shahzad Hussain; Muhammad Naeem Ahmed; Muhammad Waseem (Natural Product Research, 2025)

The nexus of green innovation, cleaner production, and eco-efficiency and their role in environmental sustainability - Xin Zhang; Aitzaz Khurshid; Kanwal Zahra; Syed Nabeel Haider; Muhammad Shehzad Hanif (Gondwana Research, 2025)

Insights on Diversity and Exploitation of Sharks and Rays in the East Coast of Peninsular Malaysia - Ahmad Shaqiq Alizdi Ahmad Sharikin; Abdullah Mohamad; Muhammad Hanif Fadzli; Wan Mohamad Aiman Wan Azimi; Serena Adam; Aslina Nasir; Rumeaida Mat Piah (Thalassas: An International Journal of Marine Sciences, 2025)

Population Parameter and Spawning Potential Ratio (SPR) of Dominant Species of Groupers and Snappers in Alas Strait, West Nusa Tenggara; Implications for Future Management Measures - Hesti Pratiwi; Soraya Gigentika; Misbahul Umam; Muhammad Hanif Fadzli; Rumeaida Mat Piah (Thalassas: An International Journal of Marine Sciences, 2025)

High genetic diversity and panmictic population of Malabar trevally (Platycaranx malabaricus) - Nuralif Fakhrullah Mohd Nur; Nur Izzati Zulaidi; Muhammad Hanif Fadzli; Min Pau Tan; Siti Azizah Mohd Nor; Ying Giat Seah; Ahasan Habib; Tun Nurul Aimi Mat Jaafar (Marine Biology, 2025)

Biostratigraphy, Microfacies, and Palaeoenvironmental Dynamics of the Early Eocene Dungan Formation, Pakistan: implications for the Carbonate Ramp Evolution and Larger Foraminiferal Extinction and Origination Event (LFEO) during Global Warming - Muhammad Azhar Farooq Swati; Muhammad Hanif (Carbonates and Evaporites, 2025)

Organic matter enrichment and shale-oil bearing reservoir potential of the inter-salt shales in the eocene Bahadur Khel salt from the Kohat basin, North Pakistan - Muhammad Ishaq; Muhammad Hanif; Mohammed Hail Hakimi; Muhammad Rizwan; Samina Jahandad; Afikah Rahim; Ali Y. Kahal (Carbonates and Evaporites, 2025)

Molecular characterization of lumpy skin disease virus in the cattle population of District Lower Chitral, Khyber Pakhtunkhwa, Pakistan - Almas Faryal Nizam; Iram Maqsood; Hanif Ur Rahman; Saira Awaz; Imran Ullah Shah; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Asima Azam; Ayesha Hidayat (Antonie van Leeuwenhoek, 2025)

Paleoceanography and marine ecosystem over 250 ky offshore Southwest Western Australia; Insight from nannofossil assemblages - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Qianru Wang; Muhammad Hanif; Cong Cheng (Marine Micropaleontology, 2025)

Aftershock sequence of the Yogyakarta earthquake 2006 (Mw ~ 6.4), Indonesia, based on analysis of hypocenter relocation, static, and dynamic stress - Mohamad Ramdhan; Kadek Hendrawan Palgunadi; Muhammad Maruf Mukti; Virga Librian; Gatut Daniarsyad; Faiz Muttaqy; Edi Hidayat; Syuhada Syuhada; Muhammad Hanif; Adityo Mursitantyo; Birger-Gottfried Lühr; Andri Dian Nugraha; et al. (Natural Hazards, 2025)

Adsorptive Remediation of Cadmium Ions with Modified Plant Straw Using Response Surface Methodology - Aanisa Manzoor Shah; Inayat Mustafa Khan; Rehana Rasool; Tahir A. Sheikh; Muhammad Athar Khaliq; Shaista Nazir; Javid A. Bhat; Yasir Hanif Mir; Rifat un Nissa; Sami Al Obaid; Mohammad Javed Ansari; Shafeeq Ur Rahman (International Journal of Environmental Research, 2025)

Therapeutic applications of quercetin-metallic complexes: a review - Nasreen Ramzan; Huma butt; Muhammad Azeem; Muhammad Hanif; Khalid Mahmood; Sadia Rehman; Dure shahwar; Muhammad Zeeshan; Qurat-ul-Ain Ahmad; Mehreen Jabeen (BioMetals, 2025)

Use of magnetic nanomaterials in wastewater treatment: a review - Sara Yaqoob; Muhammad Asif Hanif (Environmental Monitoring and Assessment, 2025)

Dynamic ARDL simulations of Pakistan’s energy intensity: the role of non-fossil energy, innovation, and financial development - Muhammad Haris Hanif (Environment, Development and Sustainability, 2025)

Catharanthus roseus (L.) G. Don: A herb with the potential for curing breast cancer - Syeda Syesha Saman; Aqsa Hanif; Sawsan S. Al-Rawi; Ahmad H. Ibrahim; Muhammad Adnan Iqbal; Sabha Khalid; Adnan Majeed; Athar Mahmood; Farhan Ahmad (Next Research, 2025)

Retraction notice to “Recent advances in microstructural control via thermal spraying for solid oxide fuel cells” [Chem. React. Eng. 478 (2023) 147352] - Jiu-Tao Gao; Muhammad Bilal Hanif; Hui-u Zhang; Martin Motola; Cheng-Xin Li (Chemical Engineering Journal, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Inferring paleoenvironmental changes from integrated facies analysis of the late Paleocene-early Eocene succession, Salt Range, Pakistan - Muhammad Hanif; Mahnoor Sabba; Iftikhar Ahmed Abbasi; Mohamed Abioui; Nowrad Ali; Muhammad Ishaq (Carbonates and Evaporites, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

Superior photocatalytic and self-cleaning performance of PVDF-TiO₂@NH₂-MIL-125(Ti)/PVA membranes for efficient produced water treatment - Tutuk Djoko Kusworo; Meitri Bella Puspa; Andri Cahyo Kumoro; Muhammad Itsar Hanif; Mohd Hafiz Dzarfan Othman; Tonni Agustiono Kurniawan; Dani Puji Utomo (Journal of Water Process Engineering, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Tracking the tropical aquatic dragon: environmental DNA (eDNA) detection for monitoring the endangered Asian arowana, Scleropages formosus (Müller and Schlegel, 1840) - Norli Fauzani Mohd Abu Hassan Alshari; Muhammad Hanif Iryani Adnan; Danial Hariz Zainal Abidin; Siti Zafirah Ghazali; Min Pau Tan; Noor Adelyna Mohammed Akib; Sébastien Lavoué; Siti Azizah Mohd Nor (Hydrobiologia, 2025)

Enhanced dye removal performance of yellow stone waste powder via cadmium iron oxide coating and study of its mechanism - Rabia Shaheen; Muhammad Asif Hanif (Environmental Monitoring and Assessment, 2025)

Environmentally friendly nitrogen doped paired mineral-carbon for catalytic degradation of diethyl phthalate and crop damage mitigation - Saeed Rehman; Hongjuan Sun; Muddasir Hanif; Tongjiang Peng; Xu Tang; Osama Tariq Satti; Muhammad Bilal (Chemical Engineering Journal, 2025)

Citrus phytochemicals as potential therapeutics against asiatic citrus psyllid and Candidatus Liberibacter asiaticus: targeting the tripartite interaction - Muhammad Awais; Muhammad Ali; Mohsin Javed; Faisal Hanif; Muhammad Nouman; Ammar Zidan; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Abd-ElAziem Farouk; Ibrahim Jafri (Journal of Plant Pathology, 2025)

Assessing the influence of eucalyptus bark ash and willow wood ash on the physical, mechanical, and microstructural properties of portland cement pastes and mortars - Nazeef Ullah; Muhammad Hanif Khan; Muhammad Ali Sikandar; Zhao Qiuhong; Han Zhu; Obaid Rauf; Zaheer Farooq (Innovative Infrastructure Solutions, 2025)

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Evaluation of mechanical responses of asphalt mixtures incorporating plastic waste as additives by different compaction efforts and mixing temperatures for a sustainable mixture - Siti Nur Naqibah Kamarudin; Muhammad Naqiuddin Mohd Warid; Mohd Zul Hanif Mahmud; Haryati Yaacob; Kabiru Usman Rogo; Mohd Khairul Afzan Mohd Lazi (Environmental Science and Pollution Research, 2025)

A multi-proxy approach to explore paleoenvironmental oscillations and chronostratigraphy of Thanetian carbonates in Eastern Tethys, Pakistan - Amir Shahzad; Yasir Sirfraz; Khawaja Shoaib Ahmed; Muhammad Hanif; Muhammad Tayyib Riaz; Khawaja Shafique Ahmad; Thierry Adatte (Marine and Petroleum Geology, 2025)

Advancements in MXene-based 3D printing-based technologies - Ali Asghar; Muhammad Shahid Rashid; Muhammad Hanif; Imed Boukhris; Zhangwei Chen; Muhammad Saqib; Qumail Arshad; P. Rosaiah; Saood Ali; Iftikhar Hussain (Chemical Engineering Journal, 2025)

Correction: Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Advancing plant disease classification: A robust and generalized approach with transformer-fused convolution and Wasserstein domain adaptation - Muhammad Hanif Tunio; Jian ping Li; Xiaoyang Zeng; Awais Ahmed; Syed Attique Shah; Hisam-Uddin Shaikh; Ghulam Ali Mallah; Imam Abdullahi Yahya (Computers and Electronics in Agriculture, 2024)

Evolution of the Late Cretaceous orbitoidal foraminifera and implications for the taxonomy and biostratigraphy in the Eastern Neo-Tethys, Lower Indus Basin, Pakistan: A biometric approach - Muhammad Rizwan; Muhammad Hanif; Muhammad Ishaq (Journal of Asian Earth Sciences, 2024)

The optimization of marine geoid model from altimetry data using Least Squares Stokes modification approach with additive corrections across Malaysia - Nornajihah Mohammad Yazid; Ami Hassan Md Din; Muhammad Faiz Pa’suya; Abdullah Hisam Omar; Nazirah Mohamad Abdullah; Mohammad Hanif Hamden (International Journal of Remote Sensing, 2024)

Integration of Local Mean Sea Level and Land Vertical Datum over Peninsular Malaysia via Transformation Model - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Noorfatekah Talib; Mohamad Azril Che Aziz; Muhammad Zahir Ramli; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid (Pure and Applied Geophysics, 2024)

Association of polymorphism of NLRP3, ICAM-1, PTPN22, INS genes in childhood onset type 1 diabetes in a Pakistani population - Anjum Jabeen; Samreen Riaz; Muhammad Usman; Asia Parveen; Maryam Mukhtar; Abdul Wajid; Atif Hanif; Andleeb Batool (Molecular Biology Reports, 2024)

Molecular characterization of Peste des petits ruminants virus (PPRV) in sheep and goats and risk factors associated with it in selected districts of Khyber Pakhtunkhwa-Pakistan - Saira Awaz; Iram Maqsood; Hanif Ur Rahman; Muhammad Ijaz Ali; Baitullah Khan; Gul Muhammad; Imtiaz Ali Shah; Asima Azam; Ayesha Hidayat; Almas Faryal Nizam (Molecular Biology Reports, 2024)

Surface deformation monitoring and forecasting of sinabung volcano using interferometry synthetic aperture radar and forest-based algorithm - Muhammad Hanif; Sarun Apichontrakul; Pakhrur Razi (Remote Sensing Applications: Society and Environment, 2024)

Retraction Note: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2024)

Flexible MXenes for printing energy storage devices - Iftikhar Hussain; Onkar Jaywant Kewate; Sumanta Sahoo; Sikandar Aftab; P. Rosaiah; Muhammad Ahmad; Muhammad Bilal Hanif; Wail Al Zoubi; Zeeshan Ajmal; Waqas Ul Arifeen; Mohd Zahid Ansari; Bhargav Akkinepally; et al. (Chemical Engineering Journal, 2024)

Isomer engineering of triptycene-fused multi-resonance TADF emitters: Implications for controlling blue electroluminescence performance - Hanif Mubarok; Kyumi Lee; Rafi Muhammad Lutfi; Taehwan Lee; Young Hoon Lee; Thi Quyen Tran; Jaehoon Jung; Jeong-Hwan Lee; Min Hyung Lee (Chemical Engineering Journal, 2024)

Sedimentology and reservoir characterization of Upper Cretaceous Kawagarh Formation, Upper Indus Basin, Lesser Himalayas, Pakistan: inferences from petrography, SEM-EDS and petrophysics - Salman Ahmed Khattak; Muhammad Hanif; Sajjad Ahmad; Ihtisham Islam; George Kontakiotis; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Microplastics in agroecosystems: Soil-plant dynamics and effective remediation approaches - Muhammad Tayyab; Syed Shabi Ul Hassan Kazmi; Paolo Pastorino; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Muhammad Sajid Hanif; Waqar Islam (Chemosphere, 2024)

Surface modified ZnO NPs by betaine and proline build up tomato plants against drought stress and increase fruit nutritional quality - Saad Hanif; Snovia Farooq; Misbah Zeb Kiani; Muhammad Zia (Chemosphere, 2024)

Ypresian–Lutetian platform evolution in the Indus Basin, Southwestern Pakistan: An interplay between local and regional tectonic changes - Maqsood Ur Rahman; Muhammad Hanif; Tao Jiang; Wang Qianru; Fulong Ning; Muhammad Sarim; Muhammad Rizwan; Faheem Ahmed (Sedimentary Geology, 2024)

Integrative approach to the biochemical, and toxicological fingerprinting of Polygonum glabrum.: A computational and experimental synergy for a medicinal food plant - Sumera Hanif; Muhammad Faisal Nadeem; Haji M. Shoaib Khan; Muhammad Naeem; Anjum Khursheed; Abdulwahab Alamri; Mhdia Elhadi Osman; Adel Alghamdi; Nasrin E. Khalifa; Marcello Locatelli; Syafiq Asnawi Zainal Abidin (Food Bioscience, 2024)

Enhancing productivity and profitability of quinoa through optimization of plant spacing and weeding regimes - Muhammad Kashif Hanif; Irfan Afzal; Muhammad Kashif Munir; Abdul Khaliq; Hafiz Naeem Asghar (Field Crops Research, 2024)

Recent Development on Sensing Strategies for Small Molecules Detections - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Anser Ali; Hussain Raza; Song Ja Kim; Changrui Lu (Journal of Fluorescence, 2024)

Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Development and validation of an indirect ELISA for the serodiagnosis of contagious caprine pleuropneumonia in goats - Hayatullah Khan; Farhan Anwar Khan; Umer Sadique; Ijaz Ahmad; Muhammad Saeed; Faisal Ahmad; Faiz Ur Rehman; Hanif Ur Rahman (Small Ruminant Research, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Tailored design of CO2-selective mixed-matrix membranes using nitrile-functionalized COFs as 2D nanofillers - Bosirul Hoque; Mohd Yusuf Khan; Aamir Hanif; Mahmoud Abdelnaby; Aasif Helal; Abuzar Khan; Muhammad Usman; Qasem Ahmed Drmosh (Journal of Environmental Chemical Engineering, 2024)

Recent Advances of carbon Pathways for Sustainable Environment development - K.S. Aryamol; Kuppusamy Kanagaraj; Senthilkumar Nangan; Jozef T. Haponiuk; Manunya Okhawilai; Saravanan Pandiaraj; Muhammad Bilal Hanif; Abdullah N. Alodhayb; Sabu Thomas; Natesan Thirumalaivasan; Sreeraj Gopi (Environmental Research, 2024)

Chemical element analysis of Arjuno-Welirang igneous rocks - Hanif ‘Izzuddin Zakly; Siti Zulaikah; Cahyo Aji Hapsoro; Shofi Maulida; Muhammad Fathur Rouf Hasan (Environmental Science and Pollution Research, 2024)

Typical of Tsunami Hazard Potential from Earthquake and Landslide Sources in Palabuhanratu Bay, Indonesia - Wiko Setyonegoro; Aditya Riadi Gusman; Muhammad Hanif; Telly Kurniawan; Sri Ardhyastuti; Muhamad Mahfud Muqoddas; Mamoru Nakamura; Purna Sulastya Putra; Semeidi Husrin; Nuraini Rahma Hanifa; Septriono Hari Nugroho; Evie Hadrijantie Sudjono; et al. (Pure and Applied Geophysics, 2024)

γ-Glutamyltranspeptidase (GGT) Sensitive Fluorescence Probes for Cancer Diagnosis; Brief Review - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Hussain Raza; Kim Song Ja; Changrui Lu (Journal of Fluorescence, 2024)

Identification of synthetic wheat lines with broadly effective stripe rust resistance - Karanjeet S. Sandhu; Davinder Singh; Fikrte Y. Belayineh; Tamrat Negash; Hanif Khan; Subhash C. Bhardwaj; Suraj Baidya; Dhruba B. Thapa; Muhammad Fayyaz; Shahzad Asad; Mandeep S. Randhawa; Robert F. Park (Australasian Plant Pathology, 2024)
Wheat stripe/yellow rust (WYR), caused by Puccinia striiformis f. sp. tritici ( Pst ), is a major constraint in global wheat production. A set of 766 hexaploid synthetic wheat lines, including primary crosses of Triticum turgidum x Aegilops tauschii and their derivatives, were screened in artificially rust inoculated field nurseries for three seasons. From this set, a core set of 94 non-lodging lines with unique pedigrees and resistance to Pst that was consistent across years was established. The core set was tested for adult plant field response under field conditions for three seasons in Australia and at least one crop season in Ethiopia, India, Kenya, Nepal and Pakistan. It was also challenged with an array of well-defined Pst pathotypes at seedling growth stages in the greenhouse, and genotyped with molecular markers linked to the adult plant resistance (APR) genes Yr18 , Yr36 and Yr46 . Combined analysis of field rust responses, multi-pathotype seedling phenotyping and marker genotyping resolved seven classes of Pst resistance: uncatalogued (new) APR (UAPR, 11%), uncatalogued seedling resistance (USR, 46%), known seedling resistance (KSR, 5%), KSR + USR (2%), Yr18 + UAPR (4%), Yr18 + USR (29%) and Yr18 + KSR (3%). A majority of the lines carrying UAPR and USR either singly or in combination showed high levels of field resistance across all field sites and years of testing, demonstrating that these lines represent a valuable resource for breeding wheat for resistance to Pst .

Mesozoic structural evolution of the Northern South China Sea margin using potential field modelling - Syed Wajid Hanif Bukhari; Sanzhong Li; Jie Liu; Ze Liu; Muhammad Farhan; Ishaq Kakar (Tectonophysics, 2024)

Design, optimization and verification of a conical guiding origami mechanism for underwater docking station - Aoxiang Tian; Li Zhang; Jun Liu; Shiqi Shao; Jiayu Zheng; Nuocheng Xu; Zhaojun Chen; Muhammad Hanif (Ocean Engineering, 2024)

Samarium-based metal organic frameworks as high performance electrocatalyst for alkaline water splitting - Muhammad Mukhtar Sirati; Shagufta Sirati; Umay Amara; Ajaz Hussain; Dilshad Hussain; Muhammad Hanif; Khalid Mahmood; Hafiz Muhammad Asif; Muhammad Khalid; Muhammad Tariq; Farhan Siddique; Muhammad Yaqub; et al. (Fuel, 2024)

Isolation and characterization of Rhizobium from non-leguminous potato plants: New frontiers in Rhizobium research - Tahir Naqqash; Kauser Abdullah Malik; Asma Imran; Sohail Hameed; Muhammad Shahid; Muhammad Kashif Hanif; Afshan Majeed; Muhammad Arshad; Jan Dirk van Elsas (Biology and Fertility of Soils, 2024)

Integrated facies analysis of the Late Cretaceous Simsima Formation in northwestern Oman mountain, Jabel Al-Rawdah, Hatta area, Oman - Mithaa Salim Al-Jabri; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al Sayigh (Arabian Journal of Geosciences, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Efficient synergistic degradation of Congo red and omeprazole in wastewater using rGO/Ag@ZnO nanocomposite - Nazish Kousar; Sufian Rasheed; Kousar Yasmeen; Abdul Rehman Umar; Mouna Hind Laiche; Mohsin Masood; Haji Muhammad; Muddasir Hanif (Journal of Water Process Engineering, 2024)

Effectiveness of conservation messages to reduce households' GHG emissions: A serious-gaming experiment - Datu Buyung Agusdinata; Muhammad Hanif; Rachael Shwom; David Watkins; Kristin Floress; Cara Cuite; Kathleen E. Halvorsen (Journal of Environmental Management, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Effects of seismic risk analysis on regional sectors using both the deterministic and stochastic modeling - Muhammad Imran Hanif; Rehman Akhtar (Natural Hazards, 2024)

Effect of multiwalled carbon nanotubes on compressive behavior of concrete at elevated temperature for mass concreting - Kashan Nisar; Muhammad Shahid Siddique; Muhammad Rizwan; Syed Hassan Farooq; Muhammad Usman; Asad Hanif (European Journal of Environmental and Civil Engineering, 2023)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

RETRACTED: Recent advances in microstructural control via thermal spraying for solid oxide fuel cells - Jiu-Tao Gao; Muhammad Bilal Hanif; Hui-Yu Zhang; Martin Motola; Cheng-Xin Li (Chemical Engineering Journal, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

g-C3N4/graphene oxide/SnFe2O4 ternary composite for the effective sunlight-driven photocatalytic degradation of methylene blue - Suman Tahir; Muhammad Zahid; Muhammad Asif Hanif; Muhammad Yasir Javed (Environmental Science and Pollution Research, 2023)

National strategy for climate change adaptability: a case study of extreme climate-vulnerable countries - Noman Arshed; Muhammad Ibrahim Saeed; Sultan Salem; Uzma Hanif; Manzir Abbas (Environment, Development and Sustainability, 2023)

Inquiring the impact of rural–urban migration, construction sector, and agriculture irrigated land on environmental degradation: insights from urbanized Asian countries - Feng Guoru; Muhammad Haris Hanif; Usman Saleem Yousaf (Environmental Science and Pollution Research, 2023)

Solving the Inter-Terminal Truck Routing Problem for Delay Minimization Using Simulated Annealing with Normalized Exploration Rate - Muhammad Hanif Ramadhan; Imam Mustafa Kamal; Dohee Kim; Hyerim Bae (Journal of Marine Science and Engineering, 2023)
The growth in containerized shipping has led to the expansion of seaports, resulting in the emergence of multiple terminals. While multi-terminal systems increase port capacity, they also pose significant challenges to container transportation, particularly in inter-terminal movements. Consequently, the transportation delay of containers in inter-terminal operations demands crucial attention, as it can adversely affect the efficiency and service levels of seaports. To minimize the total transportation delays of the inter-terminal truck routing problem (ITTRP), we introduce simulated annealing with normalized acceptance rate (SANE). SANE improves the exploration capability of simulated annealing (SA) by dynamic rescaling of the transportation delay objective to modify the acceptance probability. To validate the quality of solutions provided by SANE, we have developed a mathematical model that provides a set of linear formulations for ITTRP constraints, avoiding the known set-partitioning alternative. Experimental results showed that for small-scale ITTRP instances, SANE achieved a solution close to the optimal. In larger instances with 100–120 orders, SANE found feasible suboptimal solutions within 15–21 seconds, which is unattainable using the exact solver. Further comparison with baselines indicates that SANE provides considerable improvements compared to both SA and Tabu search in terms of the objective value.

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Proline coated ZnO NPs as nanofertilizer against drought stress: an in vitro study to Coriandrum sativum - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Synergistic effect of glycine betain-ZnO nanocomposite in vitro for the amelioration of drought stress in coriander - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Titanium doped cobalt ferrite fabricated graphene oxide nanocomposite for efficient photocatalytic and antibacterial activities - Kiran Khalid; Anam Zahra; Umay Amara; Muhammad Khalid; Muhammad Hanif; Mubashir Aziz; Khalid Mahmood; Muhammad Ajmal; Muhammad Asif; Kinza Saeed; Muhammad Farooq Qayyum; Waseem Abbas (Chemosphere, 2023)

Versatile application of BiVO4/TiO2 S-scheme photocatalyst: Photocatalytic CO2 and Cr(VI) reduction - Viktoriia Liapun; Muhammad Bilal Hanif; Marcel Sihor; Xenia Vislocka; Saravanan Pandiaraj; Unnikrishnan V K; Guru Karthikeyan Thirunavukkarasu; Miroslava Filip Edelmannová; Martin Reli; Olivier Monfort; Kamila Kočí; Martin Motola (Chemosphere, 2023)

Assessment of the ultimate strength of stiffened panels of ships considering uncertainties in geometrical aspects: Finite element approach and simplified formula - Muhammad Imaduddin Hanif; Ristiyanto Adiputra; Aditya Rio Prabowo; Yasuhira Yamada; Nurman Firdaus (Ocean Engineering, 2023)

Length Frequency Distribution, Length-Weight Relationships and Growth Parameters of Coastal Trevally Turrum coeruleopinnatum (Rüppell, 1830) Caught from Terengganu Waters, Malaysia - Muhammad Hanif Fadzli; Tun Nurul Aimi Mat Jaafar; Ahmad Shaqiq Alizdi Ahmad Sharikin; Tan Min Pau; Nur Athirah Abd Latiff; Siti Asmal Mat Piah; Rumeaida Mat Piah (Thalassas: An International Journal of Marine Sciences, 2023)

How flare-up of small and medium enterprises intensifies carbon emissions in Asian and European regions: a panel analysis - Han Fei; Muhammad Haris Hanif; Imran Hanif (Environmental Science and Pollution Research, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Seaweed-derived bio-stimulant improves growth and salt tolerance of radish varieties under saline conditions - Sadaf Gul; Zainul Abideen; Muhammad Yousuf Adnan; Maria Hanif; Muhammad Farrakh Nawaz; Shumaila; Ali El- Keblawy (Biocatalysis and Agricultural Biotechnology, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Chemical composition and antimicrobial activity of Boswellia serrata oleo-gum-resin essential oil extracted by superheated steam - Muhammad Adnan Ayub; Muhammad Asif Hanif; Joanne Blanchfield; Muhammad Zubair; Muhammad Amin Abid; Muhammad Tahir Saleh (Natural Product Research, 2023)

Thermal and mechanical characterization of composite materials from industrial plastic wastes and recycled nylon fibers for floor paving tiles application - Macaulay M. Owen; Emmanuel O. Achukwu; Ahmad Zafir Romli; Abdul Halim Bin Abdullah; Muhammad Hanif Ramlee; Solehuddin Bin Shuib (Waste Management, 2023)

Cellular and Non-cellular Antioxidant Properties of Vitamin E–Loaded Metallic-Quercetin/Polycaprolactone Nanoparticles for the Treatment of Melanogenesis - Nasreen Ramzan; Muhammad Azeem; Khalid Mahmood; Shahid Shah; Fazal Rahman Sajid Chughtai; Muhammad Hanif; Nabeela Ameer; Zakia Bashir; Farhan Siddique; Muhammad Qaisar (AAPS PharmSciTech, 2023)

Optimized photodegradation of palm oil agroindustry waste effluent using multivalent manganese–modified black titanium dioxide - Rab Nawaz; Sajjad Haider; Muzammil Anjum; Vipin Kumar Oad; Adnan Haider; Rawaiz Khan; Muhammad Aqif; Tahir Hanif; Nasruulah Khan (Environmental Science and Pollution Research, 2023)

The role of natural resources, clean energy and technology in mitigating carbon emissions in top populated countries - Meihan Liu; Shi Baisheng; Majed Alharthi; Muhammad Shahid Hassan; Imran Hanif (Resources Policy, 2023)

Detailed diagenetic investigation and their impact on the reservoir potential of Upper Cretaceous mixed carbonate-siliciclastic succession, Rakhi Nala Section, Eastern Sulaiman Range, Pakistan - Muhammad Rizwan; Muhammad Hanif; Shuja Ullah; Muhammad Ishaq (Carbonates and Evaporites, 2023)

Physico-mechanical and petrographic analysis of the Margalla Hill Limestone, Islamabad, Lesser Himalaya, Pakistan - Basit Ali; Mumtaz Ali Khan; Muhammad Hanif; Masood Anwar; Beenish Ali; Mustafa Yar; Ijaz Ahmed (Carbonates and Evaporites, 2023)

Bioremediation of heavy metals polluted environment and decolourization of black liquor using microbial biofilms - Iram Liaqat; Noor Muhammad; Chaman Ara; Uzma Hanif; Saiqa Andleeb; Muhammad Arshad; Muhammad Nauman Aftab; Chand Raza; Muhammad Mubin (Molecular Biology Reports, 2023)

Microplastics in facial cleanser: extraction, identification, potential toxicity, and continuous-flow removal using agricultural waste–based biochar - Muhammad Adli Hanif; Naimah Ibrahim; Farrah Aini Dahalan; Umi Fazara Md. Ali; Masitah Hasan; Ayu Wazira Azhari; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2023)

Tectonic landform and paleoseismic events of the easternmost Matano fault in Sulawesi, Indonesia - Adi Patria; Danny Hilman Natawidjaja; Mudrik Rahmawan Daryono; Muhammad Hanif; Anggraini Rizkita Puji; Hiroyuki Tsutsumi (Tectonophysics, 2023)

Fluid source and physicochemical conditions of the polymetallic mineralization in Gawuch Formation, Kohistan Island Arc, NW Pakistan - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Dieter Garbe-Schönberg; Tao Wu; Zaheen Ullah; Zahid Hussain; Tehseen Zafar; Izhar Sadiq; Syed Wajid Hanif Bukhari; et al. (Geochemistry, 2023)

Late Pleistocene chronostratigraphy and biostratigraphy of Mentelle Basin and its implications for global correlation - Maqsood Ur Rahman; Tao Jiang; Muhammad Sarim; Muhammad Hanif; Timothy T. Barrows; Yipan Hu (Marine Geology, 2023)

Dominance of bacillus sp. alter microbiological and nutritional quality and improve aerobic stability of the corn silage - Smayia Sharif; Nafeesa Qudsia Hanif; Shakira Ghazanfar; Muhammad Imran; Mohammed A. E. Naiel; Mahmoud Alagawany (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Two-way strategy for enhanced pectinase production: Random mutagenesis and utilization of a halophytic biomass - Asma Hanif; Uroosa Ejaz; Khwaja Ali Hasan; Malaika Karim; Fehmida Suleman; Muskan Siddiq; Syed Faraz Moin; Zainul Abideen; Muhammad Sohail (Biocatalysis and Agricultural Biotechnology, 2023)

Synthesis, Characterization, Optical Properties, Molecular Modeling and Urease Inhibition Analysis of Organic Ligands and Their Metal Complexes - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Mubashir Hassan; Tehreem Tahir (Journal of Fluorescence, 2023)

Correction to: Assessment of soil-gas radon concentration over lithologies: a case study from district Karak, Khyber Pakhtunkhwa, Pakistan - Mumtaz Ali Khan; Nimat Ullah Khattak; Muhammad Hanif; Anwar Qadir (Environmental Monitoring and Assessment, 2023)

Assessment of soil-gas radon concentration over lithologies: a case study from district Karak, Khyber Pakhtunkhwa, Pakistan - Mumtaz Ali Khan; Nimat Ullah Khattak; Muhammad Hanif; Anwar Qadir (Environmental Monitoring and Assessment, 2023)

Determining satellite-based evapotranspiration product and identifying relationship with other observed data in Punjab, Pakistan - Muhammad Amin; Mobushir Riaz Khan; Sher Shah Hassan; Muhammad Imran; Muhammad Hanif; Irfan Ahmad Baig (Environment, Development and Sustainability, 2023)

Successful matrix stimulation and wax cleaning of a high water cut oil well of east Potwar region: A case study - Haris Ahmed Qureshi; Ali Ahmed Pathan; Temoor Muther; Ubedullah Ansari; Muhammad Hanif Chachar (Arabian Journal of Geosciences, 2022)

Test comparison of seeds and skins extract of duku’s fruit (Lansium domesticum Corr.) against the amount of melanin pigment of skin mencit (Mus musculus) to prevent premature aging of the skin - Delima Engga Maretha; Dini Afriansyah; Dewi Susilo Wati; Mashuri Masri; Ade Rizky Dwiyanti; Muhammad Ifham Hanif; Slamet Wardoyo (Advances in Traditional Medicine, 2022)

Biopesticides and insect pest management - Kanwal Hanif; Muhammad Zubair; Dilbar Hussain; Sikander Ali; Muhammad Saleem; Hafiz Azhar Ali Khan; Tamsila Nazir; Muhammad Waqas ul Hassan (International Journal of Tropical Insect Science, 2022)

Natural polysaccharide-based biodegradable polymeric platforms for transdermal drug delivery system: a critical analysis - Sobia Noreen; Jin-Xiang Ma; Muhammad Saeed; Fahad Pervaiz; Muhammad Farhan Hanif; Bilal Ahmed; Muhammad Irshad Farooq; Faizan Akram; Muhammad Safdar; Asadullah Madni; Muhammad Naveed; Li Chang-Xing (Drug Delivery and Translational Research, 2022)

Association between energy consumption preferences and macroeconomic stability: an empirical analysis from developing Asia - Lu Shaohua; Imran Hanif; Muhammad Gulzaib Chaudhary (Environmental Science and Pollution Research, 2022)

Hybrid geoid model over peninsular Malaysia (PMHG2020) using two approaches - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid; Mohamad Azril Che Aziz; Mohd Adhar Abd Samad (Studia Geophysica et Geodaetica, 2022)

Re-examining the nexuses of communicable diseases, environmental performance, and dynamics of sustainable Development in OECD countries - Zhang Yu; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Muhammad Sajid Amin; Laeeq Razzak; Muhammad Tariq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Geochemical investigation of low latitude black shale intervals of the Lower to Middle Jurassic succession, Indus Basin, Pakistan - Fahad Ali; Shiqi Zhang; Muhammad Hanif; Mohibullah Mohibullah; Yaxuan Zhang; Muhammad Usman; Sheng Wang; Xueliang Liu; Pengjie Ma; Dongmou Huang (Frontiers of Earth Science, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

RETRACTED ARTICLE: Low-cost novel nano-constructed granite composites for removal of hazardous Terasil dye from wastewater - Maria Khalil; Muhammad Asif Hanif; Umer Rashid; Junaid Ahmad; Ali Alsalme; Toshiki Tsubota (Environmental Science and Pollution Research, 2022)

Microfilaria Positification Test Using Real-Time PCR Technique with HRM (High-Resolution Melting) - Bagus Muhammad Ihsan; Afiat Berbudi; Ridad Agoes; Muhammad Ifham Hanif (Acta Parasitologica, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Refinement of gravimetric geoid model by incorporating terrestrial, marine, and airborne gravity using KTH method - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Mohd Yunus Mohd Yusoff; Ramazan Alpay Abbak; Mohammad Hanif Hamden (Arabian Journal of Geosciences, 2021)

The Removal of Ruthenium-Based Complexes N3 Dye from DSSC Wastewater Using Copper Impregnated KOH-Activated Bamboo Charcoal - Abu Masanizan; Chee Ming Lim; Muhammad Raziq Rahimi Kooh; Abdul Hanif Mahadi; Roshan Thotagamuge (Water, Air, & Soil Pollution, 2021)

Biomechanical analysis of three different types of fixators for anterior cruciate ligament reconstruction via finite element method: a patient-specific study - Nur Afikah Zainal Abidin; Abdul Hadi Abdul Wahab; Rabiatul Adibah Abdul Rahim; Mohammed Rafiq Abdul Kadir; Muhammad Hanif Ramlee (Medical & Biological Engineering & Computing, 2021)

Simulation-based non-linear vibration model for damage detection in RC beams - Muhammad Usman Hanif; Zainah Ibrahim; Mohammed Jameel; Khaled Ghaedi; Huzaifa Hashim (European Journal of Environmental and Civil Engineering, 2021)

The influence of feeding low and high level of Brachiaria decumbens diets on the hematology, serum biochemistry, and acute phase proteins of sheep - Kalai Vaani Muniandy; Eric Lim Teik Chung; Mimi Syazwani Jaapar; Muhammad Hazziq Mohd Hamdan; Mohd Farhan Hanif Reduan; Annas Salleh; Faez Firdaus Abdullah Jesse (Tropical Animal Health and Production, 2021)

Feasibility study and modeling of solar generated steam for heavy oil recovery - Haris Ahmed Qureshi; Temoor Muther; Ubedullah Ansari; Ali Ahmed Pathan; Muhammad Hanif Chachar (Arabian Journal of Geosciences, 2021)

Biostratigraphic investigation and depositional model of the Late Thanetian Ranikot and the Ypresian Laki formations in the subsurface of the Southern Indus Basin, Pakistan - Hussain Asghar; Muhammad Saleem Mughal; Muhammad Sabir Khan; Saeed Abbas; Muhammad Hanif; Gulfam Hussain; Muhammad Ali; Kazim Ali; Amjad Hussain (Arabian Journal of Geosciences, 2021)

First Record of Australian Sawcheek Scorpionfish, Brachypterois curvispina, (Actinopterygii: Scorpaeniformes: Scorpaenidae) From the St. Martin Island, Bangladesh - Md. Abu Hanif; Muhammad A. B. Siddik; Md. Aminul Islam; Md. Rajib Sharker (Thalassas: An International Journal of Marine Sciences, 2021)

Lithofacies and petrography of Miocene Murree Formation, Peshawar basin, NW Pakistan: implications for provenance and paleoclimate - Mustafa Yar; Muhammad Hanif; Muhammad Sajid (Arabian Journal of Geosciences, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Letter to the editor on respiratory mask using a combination of spunbond, meltblown, and activated carbon materials for reducing exposure to CO: an in vivo study - Muhammad Ifham Hanif (Environmental Science and Pollution Research, 2021)

The sedimentological and stratigraphical analysis of the Paleocene to Early Eocene Dungan Formation, Kirthar Fold and Thrust Belt, Pakistan: implications for reservoir potential - Sajjad Ahmad; Bilal Wadood; Suleman Khan; Abd Ullah; Ghazi Mustafa; Muhammad Hanif; Hasbee Ullah (Journal of Sedimentary Environments, 2020)

Sedimentological attributes of the Middle Jurassic peloids-dominated carbonates of eastern Tethys, lesser Himalayas, Pakistan - Abdus Saboor; Muhammad Haneef; Muhammad Hanif; Muhammad Azhar Farooq Swati (Carbonates and Evaporites, 2020)

Microfacies analysis and depositional environments of the Upper Cretaceous Fort Munro Formation in the Rakhi Nala Section, Sulaiman range, Pakistan - Muhammad Rizwan; Muhammad Hanif; Nowrad Ali; Maqsood Ur Rehman (Carbonates and Evaporites, 2020)

Over expression of a Chitinase 2 gene from Chinese Wild Strawberry improves resistance to anthracnose disease in transgenic Arabidopsis thaliana - Zhifeng Wen; Jinhui Bai; Lin Wang; Liping Yao; Bilal Ahmad; Muhammad Hanif; Qingxi Chen (Plant Biotechnology Reports, 2020)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

The long-run and short-run influence of environmental pollution, energy consumption, and economic activities on health quality in emerging countries - Muhammad Khalid Anser; Imran Hanif; Xuan Vinh Vo; Majed Alharthi (Environmental Science and Pollution Research, 2020)

Sulfur dioxide removal: An overview of regenerative flue gas desulfurization and factors affecting desulfurization capacity and sorbent regeneration - Muhammad Adli Hanif; Naimah Ibrahim; Aishah Abdul Jalil (Environmental Science and Pollution Research, 2020)

Eocene carbonate microfacies distribution of the Chorgali Formation, Gali Jagir, Khair-e-Murat Range, Potwar Plateau, Pakistan: approach of reservoir potential using outcrop analogue - Muhammad Awais; Muhammad Hanif; Irfan U. Jan; Muhammad Ishaq; Muhammad Younis Khan (Arabian Journal of Geosciences, 2020)

Lipospheres for Simultaneous Controlled Release and Improved Pharmacokinetic Profiles of Saxagliptin-Enalapril: Formulation, Optimization, and Comparative In Vitro-In Vivo Evaluation - Safirah Maheen; Akhtar Rasul; Muhammad Hanif; Hafeez Ullah Khan (AAPS PharmSciTech, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Estimation of rare and clustered population mean using stratified adaptive cluster sampling - Muhammad Nouman Qureshi; Cem Kadilar; Muhammad Hanif (Environmental and Ecological Statistics, 2020)

Long-term ENSO relationship to precipitation and storm frequency over western Himalaya–Karakoram–Hindukush region during the winter season - Shahzad Kamil; Mansour Almazroui; In-Sik Kang; Muhammad Hanif; Fred Kucharski; Muhammad Adnan Abid; Fahad Saeed (Climate Dynamics, 2019)

Microfacies and diagenetic studies of the early Eocene Sakesar Limestone, Potwar Plateau, Pakistan: approach of reservoir evaluation using outcrop analogue - Muhammad Ishaq; Irfan U. Jan; Muhammad Hanif; Muhammad Awais (Carbonates and Evaporites, 2019)

Relating petrophysical parameters to petrographic interpretations in carbonates of the Chorgali Formation, Potwar Plateau, Pakistan - Muhammad Awais; Muhammad Hanif; Muhammad Younis Khan; Irfan U. Jan; Muhammad Ishaq (Carbonates and Evaporites, 2019)

Intraspecific morphometric diversity of barramundi (Lates calcarifer Bloch, 1790) in the waters of southern Bangladesh - Md Reaz Chaklader; Ashfaqun Nahar; Md Abu Hanif; Muhammad A. B. Siddik (Journal of Oceanology and Limnology, 2019)

Reporting effective extraction methodology and chemical characterization of bioactive components of under explored Platycladus orientalis (L.) Franco from semi-arid climate - Rafia Rehman; Muhammad Asif Hanif; Muhammad Zahid; Rashid Waseem Khan Qadri (Natural Product Research, 2019)

Potential treatment of atopic dermatitis: tolerability and safety of cream containing nanoparticles loaded with hydrocortisone and hydroxytyrosol in human subjects - Muhammad Irfan Siddique; Haliza Katas; Adawiyah Jamil; Mohd Cairul Iqbal Mohd Amin; Shiow-Fern Ng; Mohd Hanif Zulfakar; Syed Maaz Nadeem (Drug Delivery and Translational Research, 2019)

Biomechanical features of six design of the delta external fixator for treating Pilon fracture: a finite element study - Muhammad Hanif Ramlee; Mohd Ayub Sulong; Evelyn Garcia-Nieto; Daniel Angure Penaranda; Antonio Ros Felip; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2018)

Understanding the interactions of diruthenium anticancer agents with amino acids - Alexey A. Nazarov; Maria-Grazia Mendoza-Ferri; Muhammad Hanif; Bernhard K. Keppler; Paul J. Dyson; Christian G. Hartinger (JBIC Journal of Biological Inorganic Chemistry, 2018)

Finite element analysis of the wrist in stroke patients: the effects of hand grip - Muhammad Hanif Ramlee; Gan Kok Beng; Nazri Bajuri; Mohammed Rafiq Abdul Kadir (Medical & Biological Engineering & Computing, 2018)

In vitro evaluation of the potential therapeutic role of Dendropanax morbifera extract in ameliorating osteoporosis and resultant bone impairment using MC3T3-E1 cells - Dong-Uk Yang; Muhammad Hanif Siddiqi; Sungeun Ahn; Sera Kang; Hae-Yong Noh; Deok-Chun Yang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Earliness index deters Pectinophora gossypiella incidence on advanced cultivars of Bt cotton - Muhammad Rafiq Shahid; Muhammad Shakeel; Muhammad Farooq; Muhammad Shahid Arain; Chaudhary Muhammad Shahid Hanif; Haichen Yin; Muhammad Akram; Saghir Ahmad (Arthropod-Plant Interactions, 2018)

A Brief Review on Fluorescent Copper Sensor Based on Conjugated Organic Dyes - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif; Muhammad Ashraf Shaheen; Sung-Yum Seo (Journal of Fluorescence, 2018)

Thiolation of arabinoxylan and its application in the fabrication of controlled release mucoadhesive oral films - Muhammad Hanif; Muhammad Zaman (DARU Journal of Pharmaceutical Sciences, 2017)

Comparative studies of three novel freshwater microalgae strains for synthesis of silver nanoparticles: insights of characterization, antibacterial, cytotoxicity and antiviral activities - Muneeba Khalid; Nauman Khalid; Iftikhar Ahmed; Rumeza Hanif; Muhammad Ismail; Hussnain Ahmed Janjua (Journal of Applied Phycology, 2017)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Ginsenoside F1 attenuates lipid accumulation and triglycerides content in 3T3-L1 adipocytes with the modulation of reactive oxygen species (ROS) production through PPAR-γ/JAK2 signaling responses - Shakina Yesmin Simu; Muhammad Hanif Siddiqi; Sungeun Ahn; Verónica Castro-Aceituno; Natarajan Sathish Kumar; Zuly Elizabeth Jimenez Perez; Deok-Chun Yang (Medicinal Chemistry Research, 2017)

Organic Material Based Fluorescent Sensor for Hg2+: a Brief Review on Recent Development - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif (Journal of Fluorescence, 2017)

Therapeutic potential of compound K as an IKK inhibitor with implications for osteoarthritis prevention: an in silico and in vitro study - Sera Kang; Muhammad Hanif Siddiqi; Sung Joo Yoon; Sungeun Ahn; Hae-Yong Noh; Natarajan Sathish Kumar; Yeon-Ju Kim; Deok-Chun Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Evaluation of source rocks using one dimensional maturity modeling in Lower Indus Basin, Pakistan - Faisal Qayyum; Muhammad Hanif; Muhammad Mujtaba; Sohail Wahid; Fahad Ali (Arabian Journal of Geosciences, 2016)

Ginsenoside Rg5:Rk1 attenuates TNF-α/IFN-γ-induced production of thymus- and activation-regulated chemokine (TARC/CCL17) and LPS-induced NO production via downregulation of NF-κB/p38 MAPK/STAT1 signaling in human keratinocytes and macrophages - Sungeun Ahn; Muhammad Hanif Siddiqi; Veronica Castro Aceituno; Shakina Yesmin Simu; Jinglou Zhang; Zuly Elizabeth Jimenez Perez; Yu-Jin Kim; Deok-Chun Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Chemical characterisation of bioactive compounds in Medicago sativa growing in the desert of Oman - Muhammad Asif Hanif; Ahmed Yahya Al-Maskari; Jamal Nasser Al-Sabahi; Ibtisam Al-Hdhrami; Muhammad Mumtaz Khan; Ahlam Al-Azkawi; Abdullah Ijaz Hussain (Natural Product Research, 2015)

Effect of ethylene glycol dimethacrylate on swelling and on metformin hydrochloride release behavior of chemically crosslinked pH–sensitive acrylic acid–polyvinyl alcohol hydrogel - Muhammad Faheem Akhtar; Nazar Muhammad Ranjha; Muhammad Hanif (DARU Journal of Pharmaceutical Sciences, 2015)

Bioanalytical evaluation of Cinnamomum zeylanicum essential oil - Muhammad Saleem; Haq Nawaz Bhatti; Muhammad Idrees Jilani; Muhammad Asif Hanif (Natural Product Research, 2015)

The Early Cambrian Khewra Sandstone, Salt Range, Pakistan: endorsing southern Indian provenance - Mubashir Jehangiri; Muhammad Hanif; Muhammad Arif; Irfan U. Jan; Sajjad Ahmad (Arabian Journal of Geosciences, 2015)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

Arthrobacter ginsengisoli sp. nov., isolated from soil of a ginseng field - Muhammad Zubair Siddiqi; Yeon-Ju Kim; Van-An Hoang; Muhammad Hanif Siddiqi; Md. Amdadul Huq; Deok-Chun Yang (Archives of Microbiology, 2014)

Erratum to: The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

The inner ramp facies of the Thanetian Lockhart Formation, western Salt Range, Indus Basin, Pakistan - Muhammad Hanif; Muhammad Imraz; Fahad Ali; Muhammad Haneef; Abdus Saboor; Shahid Iqbal; Sajjad Ahmad (Arabian Journal of Geosciences, 2014)

Integrated stratigraphy and palaeoenvironment of the P/E boundary interval, Rakhi Nala section, Indus Basin (Pakistan) - Muhammad Hanif; Malcolm B. Hart; Stephen T. Grimes; Melanie J. Leng (Arabian Journal of Geosciences, 2014)

Lepiota vellingana sp. nov. (Basidiomycota, Agaricales) a new species from Lahore, Pakistan - Rizwana Nawaz; A. N. Khalid; Muhammad Hanif; A. Razaq (Mycological Progress, 2013)

Synthesis, crystal structure and β-glucuronidase inhibition activity of some new hydrazinecarboxamides and their 1,2,4-triazole derivatives - Muhammad Hanif; Imtiaz Khan; Nasim Hasan Rama; Shagufta Noreen; Muhammad Iqbal Choudhary; Peter G. Jones; Mazhar Iqbal (Medicinal Chemistry Research, 2012)

Salt-induced modulation in growth, photosynthetic capacity, proline content and ion accumulation in sunflower (Helianthus annuus L.) - Muhammad Shahbaz; Muhammad Ashraf; Nudrat Aisha Akram; Asma Hanif; Shumaila Hameed; Sundus Joham; Rehana Rehman (Acta Physiologiae Plantarum, 2011)

Evaluation of pollution load of Lahore Canal by quantification of various pollutants through physicochemical characterisation - Muhammad Waseem Mumtaz; Muhammad Hanif; Hamid Mukhtar; Zahoor Ahmed; Sumaira Usman (Environmental Monitoring and Assessment, 2010)

Development and Evaluation of Hydrophilic Colloid Matrix of Famotidine Tablets - Muhammad Harris Shoaib; Saniah Al Sabah Siddiqi; Rabia Ismail Yousuf; Kamran Zaheer; Muhammad Hanif; Saeed Rehana; Sabahat Jabeen (AAPS PharmSciTech, 2010)

Kinetic and Equilibrium Modeling for Cr(III) and Cr(VI) Removal from Aqueous Solutions by Citrus reticulata Waste Biomass - Ammara Zubair; Haq Nawaz Bhatti; Muhammad Asif Hanif; Faiza Shafqat (Water, Air, & Soil Pollution, 2008)

Production and characterization of a highly active cellobiase from Aspergillus niger grown in solid state fermentation - Muhammad Ibrahim Rajoka; Muhammad Waheed Akhtar; Atif Hanif; A. M. Khalid (World Journal of Microbiology and Biotechnology, 2006)